PERAN KEPEMIMPINAN PENDIDIKAN DALAM MENGELOLA KONFLIK MELALUI KOMUNIKASI ORGANISASI DI LEMBAGA PENDIDIKAN - Mardiyah Mardiyah; Arasya Meyliani Zahra; Rifda Quena Aliya Maulana; Syafa’atul Fauziah; Velina Rahmania (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study is motivated by the increasing conflicts in educational institutions caused by differences in perception, interests, and ineffective communication. This study aims to analyze the role of educational leadership in managing conflicts through organizational communication. The method used is qualitative research with a library research approach by analyzing relevant scientific literature. The results show that organizational communication plays a significant role in reducing conflict, improving working relationships, and creating a harmonious environment. Effective communication, especially open and two-way communication, can minimize misunderstandings and accelerate conflict resolution. In conclusion, communicative and participatory leadership is the key to effective conflict management in educational institutions. The implication of this study highlights the importance of strengthening organizational communication as a strategy to create stability and effectiveness in educational organizations.